2017
DOI: 10.1097/mib.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated Receptor 1 Plays a Proinflammatory Role in Colitis by Promoting Th17-related Immunity

Abstract: This study demonstrates a strong link between PAR1 expression, Th17-type immunity, and disease severity in both pediatric patients with Crohn's disease and C. rodentium-induced colitis in mice. The data presented suggest PAR1 exerts a proinflammatory role in colitis in both humans and mice by promoting a Th17-type immune response, potentially by supporting the production of IL-23.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 63 publications
3
42
0
1
Order By: Relevance
“…These endogenous proteases are massively increased in various diseases, including inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), and ischemia (7,8,31,43,56). In addition, the molecular expression of both PAR1 and PAR2 are altered in patients with IBD and IBS (3,9,38,42,48). Therefore, PAR activation may affect colonic dysmotility in patients with IBD and IBS.…”
Section: Discussionmentioning
confidence: 99%
“…These endogenous proteases are massively increased in various diseases, including inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), and ischemia (7,8,31,43,56). In addition, the molecular expression of both PAR1 and PAR2 are altered in patients with IBD and IBS (3,9,38,42,48). Therefore, PAR activation may affect colonic dysmotility in patients with IBD and IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate an increase in proteases in in ammatory bowel disease [16]. The statistically lower activity of proteases in our patients with IBD in comparison to the control group may be a response to treatment.…”
Section: Discussionmentioning
confidence: 41%
“…Excessive or poorly controlled in ammation is the central aspect of IBD. Host factors which regulate this in ammatory response play a crucial role in the pathophysiology of IBD [16]. The activity of proteases must be strictly regulated to prevent inappropriate and often destructive proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that IL-17 is produced mainly by Th17-type lymphocytes in colon tissue of colitis 37,38 . Some studies have also pointed out that IL-17 is also largely secreted by γδT cells 39,40 or CD8 + T cells 41,42 . This study found that MA could reduce the level of IL-17 and the number of γδT17 cells in colon tissues of colitis mice, and attenuate colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that IL-17 is produced mainly by Th17-type lymphocytes in colon tissue of colitis 37 , 38 . Some studies have also pointed out that IL-17 is also largely secreted by γδT cells 39 , 40 or CD8 + T cells 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%